Analysis of Factors in Early Childhood Stunting Mitigation in Disaster-Prone Areas of Sukabumi Regency - dedi Wahyudin; Herlina Lidiyawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Sukabumi Regency is a disaster-prone area. Throughout 2024, Sukabumi Regency experienced 787 landslides, 396 floods, and 49 earthquakes. In the health sector, Sukabumi Regency also faces a fairly serious stunting problem. The 2023 Indonesian Health Survey (SKI) found that stunting prevalence reached 27%, making it one of the top five districts with the highest stunting prevalence in West Java Province. The purpose of this study is to examine the risk variables that contribute to stunting mitigation. stunting in early childhood in disaster-prone areas of Sukabumi Regency. The study population consisted of all mothers with children aged 0–59 months residing in the study area. The sample size was calculated using the Lemeshow formula based on a stunting prevalence of 27% in Sukabumi Regency, resulting in a total of 303 respondents. A two-stage probability sampling method was applied, with sample allocation across locations determined using proportional random sampling, followed by respondent selection through cluster random sampling within each area. This study employed a correlational design with a cross-sectional approach. Data were collected through structured interviews using a standardized questionnaire. Univariate analysis was performed using frequency distributions, bivariate analysis employed the chi-square test, and multivariate analysis was conducted using multiple logistic regression. 41.9% of respondents had mitigation. stunting is less, 57.4% socioeconomic is less, 22.1% said access to health services is difficult to reach, 47.5% family food security is less and 61.7% family sanitation is less good, the results of the bivariate analysis showed that there is a relationship between food security, socioeconomic, access to health services, family sanitation towards mitigation stunting with p value (0.000-0.015)<0.05, multivariate analysis found that food security is the dominant factor influencing stunting stunting where , families with less food security are 10.6 times more likely to experience mitigation Lack of stunting . Conclusion: Mitigation Stunting in early childhood in disaster-prone districts in Sukabumi Regency is influenced by family sanitation, food security, socioeconomic factors, and accessibility to health services. Food security is a dominant factor influencing mitigation stunting.